Geochronology and geochemistry of early‐middle Silurian intrusive rocks in the Lanzhou–Baiyin regions, eastern part of Qilian Block, NW China: Source and tectonic implications. (28th November 2017) - Li, Xi‐Yao; Li, San‐Zhong; Zhao, Shu‐Juan; Somerville, I.D.; Guo, Xiao‐Yu; Yu, Sheng‐Yao; Huang, Zeng‐Bao; Cao, Hua‐Hua; Huang, Xing‐Fu
Abstract : The Qilian Block is one of many continental blocks involved in the early Paleozoic orogenesis of the Central China Orogen, which experienced complex interaction with adjacent blocks and orogens. In this study, we present zircon U–Pb–Hf isotopic, whole‐rock elemental, and Sr–Nd isotopic data of the early‐middle Silurian intrusive rocks in the Lanzhou–Baiyin regions, eastern part of the Qilian Block, to constrain their source and tectonic settings. The Houchangchuan granodiorite and Shichuan monzogranite were emplaced at ca. 437 Ma and ca. 428 Ma, respectively. These granitoids are peraluminous (A/CNK = 1.1–1.3), enriched in LREEs and LILEs (Rb, Th, U, Pb), depleted in HFSEs (Nb, Ta) with negative Eu and Sr anomalies, and have relatively high whole‐rock εNd (t), −4.3 to −2.1, and zircon εHf (t), −10.9 to 1.1, values. The Shichuan monzonite is characterized by intermediate SiO2, metaluminous (A/CNK = 0.8), and high LREEs fractionation with LILEs (Th, U, Pb) enrichment and HFSEs (Nb, Ta) depletion. We suggest the Houchangchuan granodiorite and Shichuan monzogranite were derived from the metasedimentary (metapelitic) source, which could be the Mesoproterozoic basement of the Qilian Block, and the mantle‐derived materials injected into their source region. The Shichuan monzonite could have a mantle‐derived origin. Integrated with data from previous studies, the early‐middle Silurian (437–428 Ma) intrusive rocks in the eastern part of the Qilian Block were formed during the transition period from a syn‐collisional to postcollisional setting, relating to the collisional process after the consumption of North Qilian Ocean (Proto‐Tethys Ocean) in the northern margin of the Gondwana continent.